Efeitos da fotobiomodulação transcraniana associada ao exercício no desempenho motor e cognitivo de camundongos - Tremarin, Renata Ferreira de Guzzi (2024)
Physical and cognitive changes inherent to the aging process are a concern given the growing elderly population. Behavioral interventions to slow functional decline while maintaining a healthy standard of living are widely studied. Developing safe therapies with proven biological and neurophysiological effects requires the use of non-clinical animal models to predict human outcomes. Non-invasive brain stimulation and physical exercise are non-pharmacological interventions attracting attention due to their lack of associated adverse events, robust safety profile, and potential to improve motor and cognitive functions by reducing inflammation, promoting cell proliferation, and mitigating oxidative stress. Few studies explore the combined effects of photobiomodulation and exercise in this context, so the present study aims to evaluate behavioral responses and neuroprotective effects in middle-aged mice subjected to transcranial photobiomodulation therapy and physical exercise. The hypothesis is that these interventions improve cognitive and motor function after 10 days. Methods: Fifty male Swiss albino mice, aged 8–10 months, were divided into groups: one receiving ten daily photobiomodulation sessions (PBM+S), one with inactive photobiomodulation (SHAM+S), one combining photobiomodulation and running wheel exercises (PBM+E), a fourth group with inactive photobiomodulation and exercise (SHAM+E), and a control group. Behavioral analyses included memory tests (object recognition test), motor performance (rotarod test), and general locomotion (open field test). Statistical analyses utilized STATA software, with parametric data analyzed using one-way ANOVA and non-parametric data via Kruskal-Wallis tests, followed by post-hoc analysis and Bonferroni correction. Results: Significant differences emerged in memory performance among groups. The SHAM+E group showed higher memory values compared to PBM+S (z = 2.496, p = 0.0125), while the PBM+S group exhibited significantly lower memory values than SHAM+S (z = -2.451, p = 0.0143). No significant differences were found in other variables. Conclusion: Photobiomodulation alone facilitated memory improvement in mice, independent of exercise. Conversely, exercise also produced an effect, though of lesser magnitude. These findings suggest that in healthy middle-aged mice, photobiomodulation alone can enhance cognitive function, but its combination with exercise did not yield the same performance, warranting further studies for application to other populations and parameters.